1987
DOI: 10.1016/0304-3959(87)90085-6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate response of phantom limb pain to calcitonin

Abstract: We applied calcitonin in a single-shot treatment to 10 patients with persistent or acute phantom limb pain. Nine patients responded immediately and noted a clear analgesic effect. In contrast a group of non-phantom pain patients of heterogeneous composition did not respond at all, except 1 patient with chronic stump pain. We believe that this could be an exciting new approach to the treatment of phantom limb pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 4 publications
0
14
0
6
Order By: Relevance
“…Direct epidural or subarachnoidal injection of CT has also shown án analgesic effect [82,83]. Besides pain management in osteoporosis [77,[84][85][86] CT has shown analgesic action in painful conditions such as phantom limb pain [87,88], diabetic neuropathy [89], complex regional pain syndrome [90], adhesive capsulitis [91,92], rheumatoid arthritis [93], vertebral crush fractures [94,95], spondylitis, tumor metastasis [96], cancer pain [97], migraine [98,99], Paget's disease of bone [100]) as well as post-operative pain [101].…”
Section: Does Calcitonin Improve Bone Quality?mentioning
confidence: 96%
“…Direct epidural or subarachnoidal injection of CT has also shown án analgesic effect [82,83]. Besides pain management in osteoporosis [77,[84][85][86] CT has shown analgesic action in painful conditions such as phantom limb pain [87,88], diabetic neuropathy [89], complex regional pain syndrome [90], adhesive capsulitis [91,92], rheumatoid arthritis [93], vertebral crush fractures [94,95], spondylitis, tumor metastasis [96], cancer pain [97], migraine [98,99], Paget's disease of bone [100]) as well as post-operative pain [101].…”
Section: Does Calcitonin Improve Bone Quality?mentioning
confidence: 96%
“…For example, parenteral salmon calcitonin was significantly more effective than placebo in reducing the frequency of pain episodes in migraine [147,148]. Likewise, calcitonin was able to reduce the pain score in patients with the phantom limb pain syndrome in the early postoperative period [149,150] and in mild cases of lumbar spinal stenosis [146]. In this condition, calcitonin has also been reported to improve physical performance and lengthen the walking distance [151].…”
Section: Clinical Evidencementioning
confidence: 95%
“…83 This is in contrast to studies in OVX and CCI rats, which showed that repeated systemic administration of CT is needed to produce analgesia. 3,4,18,76,9799 Therefore, other unknown factors may be involved in the underlying mechanism of CT in relieving oxaliplatin- and paclitaxel-induced neuropathy (Figure 5).
Figure 4.Proposed mechanism of inhibition of abnormal expression of 5-HT 1A -like receptors and sodium channels by CT in OVX rats.
…”
Section: Site Of Action Of Ct In Other Modelsmentioning
confidence: 99%